Characteristics and Genesis of Soils Developed on Low Physiographic Position on Different Textured Alluvial Plains in Arid Rajasthan - Choudhari, J S (Annals of Arid Zone, 2016)
Pedons on lower physiographic positions in coarse and medium to moderately fine textured older alluvial plains were studied for theircharacteristics and genesis. Soils (P1) on coarse textured plain are yellowish brown, columnar, having illuvial B horizon with carbonatic eyes and well formed lime segregations. In medium to moderately fine textured plain the soils (P2) are grey and prismatic. with small rounded lime segregations. Micromorphology showed the presence of crescentic coatings of fine material and also pseudomorphic infillings in voids and channels with calcitic pedofeatures in p1 whereas P2 showed limpid clay domains and infillings ofsparitic calcite crystals. Lime segregations, present throughout in both pedons were soft concretions and nodules in P1 and hard concert ions in P2. Beside these, both the soils vary in mechanical and elemental constituents. Leaching of lime and formation of segregations are pedogenic processes operated in the profile development of P2 whereas beside these illuviation and in situ weathering in P1 soils.